Barriers to Achieving Conservation Engineering Goals in Commercial Trawl Fisheries - Murphy, Robert; Yochum, Noëlle; Wolf, Nathan; Kroska, Anita C.; Harris, Bradley P. (Frontiers in Marine Science, 2022)
The advancement of conservation practices in global trawl fisheries has been impeded in part by a lack of a collective understanding of the most relevant and broad-scale knowledge-needs, along with the identification of potential barriers to addressing these knowledge-needs. Using both an online survey and an in-person workshop, we engaged a diversity of fishing industry stakeholders including scientists, technology companies, trawl net makers, and fishermen working with North Pacific, USA, trawl fisheries to identify and prioritize areas in which further knowledge is required for successful implementation of conservation engineering practices. In addition, we identified barriers to addressing these knowledge-needs. Knowledge-needs related to fishing gear performance were identified among the top priorities, including several areas targeted at improving fishing efficiency that could further advance the sustainability of well-managed trawl fisheries. To better understand the composition and behavior of target versus non-target catch, workshop participants identified the importance of closing data and technology gaps. This highlights areas for potential collaboration between fishermen, researchers, and technology companies to address research prioritized by the end-user. Further, results from the workshop emphasized a need for industry-driven training and workshops focused on elevating fishermen skill for newer entrants through peer-learning and knowledge-sharing to achieve objectives like better non-target avoidance and increased fishing efficiency of the target species. Addressing these prioritized knowledge-needs, by first working towards overcoming the industry-identified barriers, may aid in increasing uptake of conservation practices, thereby contributing to the long-term sustainability of these fisheries and associated social-ecological systems.